Identifying and investigating the foreign model's educational entrepreneurship in higher education and implement native models for Iran - Sara Shahidi (International Journal of Education and Humanities, 2022)
In today's competitive world, universities and organizations are successful and able to make the most of information and knowledge. For this reason, many universities have started knowledge orientation through entrepreneurship education. In this research, the researcher seeks to identify and study the foreign models of entrepreneurship education, documents of entrepreneurship centers of Tehran universities in higher education, and finally, develop a native Iranian model for entrepreneurship education. In this study, to identify the elements of the native model of entrepreneurship education, a qualitative approach and thematic analysis method, and MAXQDA software have been used. Therefore, first, 50 foreign standard models of entrepreneurship education, as well as documents of entrepreneurship centers of Tehran universities, were identified and selected by the researcher. Then all keywords inside the templates and documents were coded, and 735 open source codes were sent separately to specialists. Cohen Kappa value was calculated using SPSS 23 software. Findings showed that the data obtained from the study of foreign models of entrepreneurship education and documents of entrepreneurship centers of Tehran universities were classified into three categories of capability-oriented, personality-oriented, and lesson-oriented themes, which can be used to design a native model of entrepreneurship education in higher education